Motivasi Guru SD dalam Pelatihan Pembuatan Buku Berbasis Kearifan Lokal Indragiri Hulu - Alpusari, Mahmud; Copriady, Jimmi; Anggriani, Mitha Dwi; Marhadi, Hendri; Erlisnawati, Erlisnawati; Guslinda, Guslinda; Fatmawilda, Fatmawilda (Journal Of Human And Education (JAHE), 2024)
The local wisdom-based book-making training at SDN 021 Air Molek II was motivated by the urgent need to preserve Indragiri Hulu's local wisdom. The phenomenon of diminishing cultural knowledge among the younger generation is a major concern, as many children today no longer recognize or appreciate their own local culture. The aim of this training is to improve teachers' skills and motivation in writing books that integrate local cultural values and enrich students' learning experiences. The training methods include material preparation, theory on local wisdom and book-making techniques, hands-on practice, and a thorough evaluation of the activities and book results. The results show a significant improvement in teachers' skills and motivation. The resulting books are expected to not only enrich teaching materials but also help preserve local culture, giving students a deeper insight into their cultural heritage. The success of this training has the potential to serve as a model for similar initiatives in other schools, expanding the positive impact in cultural preservation and education quality improvement.